The Impact of Administrative Division and Reorganization on the Urban Network in Hodna Region (M’sila, Algeria), Spatial-Temporal Approach - Abbas , Saliha; Haddad , Louiza (Dirasat: Human and Social Sciences, 2024)
Objectives: This study aims to achieve two main objectives. The first one is determining the characteristics of the municipal network in the Hodna region and describing the most prominent spatial imbalances. The second is the impact of administrative divisions and regional reorganization processes on the spatial distribution and evolution of the population. Methods: The approach adopted in determining the characteristics of the municipal network and evaluating the degree of spatial efficiency is the descriptive, analytical and measurement approach through the application of the shape index and the polygons of Thiessen. The analysis of variation in the spatial distribution of population and spatio-temporal dynamics according to administrative divisions was through the spatio-temporal approach. Results: The results show that the municipalities shapes do not correspond to any spatial logic, as their forms are old and depend on the terrain or social factors. The reorganization of 1974 and 1984 contributed to the reinforcement of the capacities of province and the municipalities by equipping them with new urban functions and many agglomerations have been promoted to extended functions, where the capitals of districts and municipalities were turned from small urban centers to real cities. Conclusions: The administrative division and reorganization of the territory has a significant impact on the urban network and the stability of the population.Therefore, the reorganization has given more finesse and flexibility to the management of the territories by providing them with various public services and administrations inherent to their respective ranks.